The Experience of Mother in Breastfeeding and Weaning Practice for Baby Under Two Years Old: A Qualitative Descriptive Study - Shinta Widiastuty Anggerainy; Mohamad Ikhsan; Siti Nurul Huda (Poltekkes Kemenkes Bengkulu, 2023)
The experience of Mother in the form of knowledge and skills influences mothers in the practice of feeding their children, both breastfeeding and complementary food as well as weaning practices in baby under two years old. This qualitative descriptive study aims to explore the experiences of mothers in the practice of breastfeeding, complementary food and weaning of baby under two years old. Data was collected from April to June 2022 in Sungai Ana Village and Baning Kota Village, Sintang District. In this study, a sample of ten mothers was conducted in-depth interviews. The results of the interviews were analyzed using the content analysis method. There were 4 themes, namely: 1) Combination of Traditional, Belief, and Modern, 2) Mother: